ANALISIS VARIABEL YANG MEMPENGARUHI STRUKTUR MODAL - Sulton Sholehudin (University of Merdeka Malang, 2017)
The aim of this study is to examine the effect of Capital Structure to the foods and beverages and pharmacy sub sector companies Listing on Indonesia Stock Exchange. In this study used six variables, including capital structure as the dependent variable, while the independent variables are profitability, liquidity, asset structure, growth opportunity, and the size company. Number of samples in this study are 22 companies with details of 14 companies from the foods and beverages sub sector and 8 companies from the pharmaceutical sub-sector. The analysis using multiple regression. The result reveals that profitability and growth opportunity variable have no effect on capital structure, both foods and beverages, pharmaceutical, as well as a test of overall sub-sector. Otherwise, the variables of liquidity and asset structure have a significant effect on both sub-sectors. Size Company Variable has a difference where the size company showed a significant result for testing per sub-sector, but the overall test of size company is not a determinant of capital structure. This indicates that liquidity, asset structure, and size company need to be managed and controlled properly in order to arrange the composition of debt in the capital structure that is efficient and effective for the company DOI : https://doi.org/10.26905/jbm.v4i1.1710